Tumors Of The Head And Neck: Detection At Stage T Using Modern Imaging Techniques (Eurasian Medical Research Periodical, 2025)
Tumors of the head and neck are characterized by an aggressive course and a high risk of late diagnosis. Despite advances in oncology, most patients are admitted to specialized centers at stages T2–T4, when the effectiveness of treatment is significantly reduced. The detection of tumors at the T₀ stage, when there are no clinical manifestations yet, but morphological and metabolic changes are already forming, is a key area of modern oncorentgenology . The article discusses the possibilities of magnetic resonance imaging (MRI), computed tomography (CT) and positron emission tomography (PET/CT) in the diagnosis of head and neck tumors in the early stages. The results of clinical observations are presented, showing that the use of multiparametric MRI and hybrid technologies can increase the detectability of subclinical forms up to 92%.